Порівняння та аналіз методів множинного доступу OFDMA та SC-FDMA у мережах мобільного зв'язку - Соловйов, П. В. (ХНУРЕ, 2023)
Addressing the trade-offs between spectrum efficiency and implementation complexity in OFDMA and SC-FDMA technologies, mitigating the impact of high PAPR on signal quality and energy consumption, adapting modulation and coding schemes for optimal radio spectrum utilization, and coordinating multiple access management in mobile communication networks.
Keywords: методи множинного доступу